People's Republic of China : Hong Kong Special Administrative Region; 2008 Article IV Consultation Discussions; Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2008)
This paper examines the People's Republic of China's Hong Kong Special Administrative Region's 2008 Article IV Consultation. Growth has slowed in the first half of the year, as external conditions have worsened. Inflation remains elevated, driven by food prices and housing costs. The fallout from the global credit turmoil has spilled into local markets, with equity prices falling markedly and signs of stress in interbank markets. The authorities have responded with a range of measures to provide liquidity, stimulate domestic demand, and bolster confidence.